De “naturaleza”/”voluntad” a “casos oblicuos”/”caso recto” en el De lingua latina de Varrón (Minerva, 2019)
Varro, in his De lingua Latina, makes use of the confrontation between the voluntary and the involuntary to denominate and give account of certain linguistic realities. He starts from the opposition natural uoluntas and from its derivatives, as Cicero uses them and as the Greek authors employ their equivalents. But he changes the sign of their terms and so he advances to the creation of a totally metalinguistic words. What he wants to explain are particular aspects of the linguistic system, understood this one not only as something static but as an authentic ability of the speaker, that's to say, as competence.